Analisis Perbandingan Birokrasi Dalam Proses Pengurusan Dan Penerbitan Surat Ijin Mengemudi (SIM) Di Indonesia Dan Malaysia - Fau, Hironimus Odaligonama; Dompak, Timbul; Khairina, Etika (Prosiding, 2024)
This research aims to explore further the bureaucratic procedures in managing the issuance of driving licenses (SIM) in Indonesia and Malaysia. This research was conducted in order to obtain an objective comparison of SIM processing procedures in the two countries and compare the efficiency of the two. The method used in this research is a qualitative research approach using literature study. The data sources used are secondary data sources originating from books, journal articles and statutory regulations. The results of this research are as follows. First, there are similarities between the SIM processing bureaucracy in Indonesia and Malaysia. These similarities include the requirement for prospective SIM holders to submit a copy of their identity card as well as a certificate of mental and physical health. This requirement is required in the SIM issuance process as a basis for recording the identity of the SIM holder and ensuring that the prospective SIM holder is truly fit for health to drive a vehicle. Apart from that, you are also required to sign and provide fingerprints for forensic purposes for the police. In other words, both Indonesia and Malaysia have similarities in terms of SIM functionality as a means for the police to regulate traffic users. Second, Malaysia lies in the systematics of driving a driver's license. Malaysia implements a driving training phase that also includes theoretical and practical testing on the road. This aims to ensure that prospective SIM holders are truly qualified to drive. Meanwhile in Indonesia there is no training system that is integrated with the SIM issuance system. There are only theory and practical exams to test general knowledge of traffic rules and driving skills for prospective SIM holders. Thus, the SIM processing bureaucracy in Indonesia is more efficient and faster when compared to Malaysia.